The baby-sitter II - Stine, R. L. (New York : Scholastic, 1991)
Jenny's last baby-sitting job nearly killed her, but she survived and now has another job. When the phone rings, she hears the familiar voice from the grave!
Keywords: Babysitters -- Fiction; Horror stories; Horror fiction